ONLINE TRAINING ON THE INTRODUCTION AND HANDLING OF THE THREAT OF RATTLESNAKES DURING THE COVID-19 PANDEMIC: PELATIHAN ONLINE PENGENALAN DAN PENANGANAN ANCAMAN ULAR BERBISA DI MASA PANDEMI COVID-19 - Agus Pambudi Dharma; Winarno (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2021)
Snakes are cold-blooded reptiles that are often found from the lowlands, headlands, soil, trees, freshwater, brackish water, to seawater, except in areas with low temperatures such as the poles. Rattlesnake bites continue to occur anytime and anywhere. Although, currently, there is a covid-19 pandemic in Indonesia. The community needs to know and identify some basic knowledge about snakes. This training was held on April 22, 2020. The method used in this training was demonstration and question and answered through the chat column on Instagram and YouTube accounts for 1 hour. The results of this online training provide additional information and knowledge to the broader community. Also, the number of participants who took part was more significant and scattered throughout Indonesia. Snakes with high venom have a pair of fangs in the upper jaw, and not all highly venomous snakes have triangular heads, such as Bungarus candidus (weling) and Bungarus fasciatus (welang).